2021
DOI: 10.3389/fpsyg.2021.754265
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variability in the Attribute Framing Effect

Abstract: An intriguing phenomenon that arises from decision making is that the decision maker’s choice is often influenced by whether the option is presented in a positive or negative frame, even though the options are, de facto, identical to one another. Yet, the impact of such differential framing of equivalent information, referred to as the attribute framing effect, may not be the same for every culture; rather, some cultures may be more readily influenced by the differentially valenced frames than others (i.e., sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…39 However, this effect has not been thoroughly studied in an Asian context. Finally, given that individual decision and behaviour are intrinsically linked to context and culture, [40][41][42] there are reasons to believe that vaccination nudges ought to be adapted to low and middle-income countries (LMIC) such as Malaysia. However, there exists a paucity of information for using such nudges in LMICs, with most published evidence originating from developed countries.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…39 However, this effect has not been thoroughly studied in an Asian context. Finally, given that individual decision and behaviour are intrinsically linked to context and culture, [40][41][42] there are reasons to believe that vaccination nudges ought to be adapted to low and middle-income countries (LMIC) such as Malaysia. However, there exists a paucity of information for using such nudges in LMICs, with most published evidence originating from developed countries.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…For instance, Chi et al (2013) found that similarity in relationship standards and couple communication patterns were linked to higher marital satisfaction. Moreover, East Asians, known for their higher prevention focus compared to Americans (Cheon et al, 2021), may derive greater contentment from substantial self-partner similarity. This body of work suggests that cultural contexts could moderate the role of similarity in relationship dynamics, and as such, warrants more nuanced cross-cultural explorations.…”
Section: Culture and Similaritymentioning
confidence: 99%
“…The way in which people react to the positive as well as to the negative factors that may affect their daily activities is determined by the culture that has shaped their personalities since human behavior, be it verbal or nonverbal, and is eminently culturebound [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Thus, culture, broadly defined as "the collective programming of the mind that distinguishes the members of one group or category of people from others" [34] (p. 3), influences distinctively the way in which humans communicate, as E.T.…”
Section: Socio-cultural Patterns and Communication Styles Across The ...mentioning
confidence: 99%